Fifty Key Thinkers on Development - Simon, David (London Routledge, 2006)
Fifty Key Thinkers on development is the essential guide to the world's most influential development thinkers. It presents a unique guide to the lives and ideas of leading contributors to the contested terrain of development studies from both North and South. David Simon has assembled a highly authoritative team of contributors from different backgrounds and disciplines to reflect on the lives and contributions of fifty leading development thinkers from around the world. These include: Modernisers like Kindleberger Dependencistas such as frank, Cardoso and Amin Progressives like Hirschman, Prebisch, Helleiner and Streeten
Includes index
Keywords: Planners-Biography, Economic development-Planning Economic development-Cross cultural studies Economic policy-cross cultural studies